IMPLEMENTATION OF MINIMUM SERVICE STANDARDS IN HOSPITALS IN INDONESIA Literature Review - Fauzia Yunus, Nur; Muhammad, Ikram (LP2M Universitas Bina Mandiri Gorontalo, 2023)
The Minimum Service Standards (MSS) are the requirements and measures of success and quality of healthcare services in hospitals. This research aims to describe the effectiveness of the implementation of Minimum Service Standards and the influencing factors in hospitals. To achieve this goal, the study utilizes a literature review of relevant scientific articles published online from 2020 to 2022 based on issues, methodology, and the relevance of research results. The research findings indicate that the implementation of Minimum Service Standards has not been effectively applied in hospitals and is influenced by the support of human resources, facilities, infrastructure, as well as communication and coordination in service delivery.